Application of the Concept of Strategic Human Resources Management in Improving Organizational Performance in the Vuca Era - Okta Karneli (Green Publisher Indonesia, 2022)
In improving organizational performance in this VUCA era, it requires a management or human resource management. The development of a company depends on the human resources of the company. Good management will have a positive impact on organizational performance. The purpose of this study is to determine the application of strategic human resource management (MSDMS) in an effort to contribute to improving organizational performance in the VUCA era. This study uses a qualitative approach by using a review of the literature in the Google Scholar database by looking for references from the literature review that is relevant to the case or problem to present the theory of the research problems carried out. The results of this study are one of the factors that directly affect the level of achievement of organizational performance is the management of human resources. Or in other words the management of human resources can be a determinant to improve organizational performance. The importance of strategic planning to improve organizational quality makes the implementation of strategic human resource management able to improve organizational performance in the VUCA era